A distributed approach to leadership in an academic department in a South African university: an exploratory case study - Haufiku, Kenneth David (Rhodes University, Faculty of Education, Department of Secondary and Post-School Education)
The Head of Department (HOD) position at a university has traditionally been viewed as an individual construct. However, due to the demanding nature of such a position, it is not sought-after, as it remains exclusive and unappealing to many academics. Moreover, it is a position that does not encourage inclusive leadership. Tension and role ambiguity are known to arise between the scholarly project on the one hand and management and administrative matters on the other. To address challenges associated with this singular leadership position, an academic department at a South African university adopted a distributed leadership approach in their department as a research experiment. My study was based on this research experiment. I designed this research as an exploratory case study, guided by a socio-cultural conceptualisation of distributed leadership that included a leader-plus and a practice aspect, defined as a product of the interactions of school leaders, followers and their situation. This qualitative case study aimed to describe and explain how a distributed leadership approach was understood and practised in an academic department. It also investigated the enablements and constraints of the approach. Data were generated through document analysis, observation, and individual and focus group interviews. The participants in this study included the departmental leadership team and the department's academic and administrative staff. Unfortunately, my study took place during the global COVID-19 pandemic and national lockdowns. I had no choice but to adapt my data generation methods due to lockdown restrictions. As a result, most data generation was done via online communication. The study used inductive and abductive analysis to make the data meaningful to the reader. The findings revealed that different participants had different ideas about distributed leadership. Distributed leadership was understood as a socio-cultural practice rather than an individual practice with multiple leaders in relational practice. In addition, this approach was understood as a way of developing and sharing expertise by encouraging teamwork, collegiality and collective decision-making which aligns with the notion of democratic decision-making which creates a platform for the enablement of leadership in others. The study further explored how distributed leadership was practised. The findings were that the HOD position, usually a one-person role, was reconceptualised as a HOD team comprised of three academics and the departmental administrator. The HOD team divided the work among themselves, and this was done according to each individual's expertise. In addition, leadership within the academic department was not limited to the HOD team but stretched across the department; thus, multiple leaders were evident. Therefore, based on the data, this study discovered that a distributed approach values leadership expertise in others. Consequently, it can be used to promote an inclusive environment in which any organisation member can lead. Inclusivity in the decision-making process was also regarded as a strong practice in the academic department. As a result, this study contends that those in formal positions can develop leadership in others through a distributed leadership approach. Through that, lecturer leadership was enacted through formal faculty and university structures and informally as and when the situation required it. The enablements of this departmental leadership approach included the structural innovation of the Friday check-in as well as the buddy system. These two innovations provided the space for collegiality and the development of voice and leadership. The consultative nature of the HOD team was also viewed as an enablement. Certain factors constrained the distributed leadership approach, one of which was the tension between the hierarchical structure of the university and the more horizontal, distributed leadership approach being piloted in the academic department. In addition to that, another constraint was also very real with the transition to Zoom as an online teaching, learning and supervision platform as a consequence of the COVID-19 pandemic. The final constraint was experienced concerning the department's history, as it was within a historically White university in South Africa. The effects of this history impacted the departmental culture and, as we know from the literature, institutional culture is extremely difficult to change. Finally, the study concluded that conceptualising distributed leadership as a sociocultural practice with leader-plus and practice aspects provides descriptive language and a solid theoretical and analytical framework for a distributed leadership study. The study makes an important knowledge contribution in the African Higher Education context as limited research has been carried out in this area. Furthermore, in terms of practice, my study serves as a stimulus for leadership discussions that are beneficial to everyone involved in educational institutions as they promote a level of leadership reflexivity, currently absent in many institutions.
Keywords: Universities and colleges Administration; Education, Higher -- South Africa; Distributed leadership; College department heads -- South Africa; School management and organization -- South Africa; Group decision making